PENGGUNAAN LKPD BERBANTUAN SIMULASI PHET DALAM MODEL PBL UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA - Dinda Aulia Mardani; Septania Nur Farida; Bambang Supriadi; Sri Apriliyani (Universitas Jember, 2023)
This research is a classroom action research with the aim of improving students' cognitive learning outcomes on alternative energy material. The subjects of this study were all 34 students of class X2 at SMAN 1 Genteng. Data collection techniques using observation methods, tests with cognitive test instruments, and documentation. Then the data was analyzed by descriptive quantitative. This research was conducted in two cycles. Each cycle consists of two meetings. The conclusion of this study is that the use of PBL model-based worksheets assisted by PhET simulations is proven to be effective in increasing students' cognitive learning outcomes. This is seen from the results of the average N-Gain scores in each cycle, namely I and II, which are 0.54 and 0.56. Both values ​​are included in the medium category, but there is an increase.